On the Effects of GATT/WTO Membership on Trade: They Are Positive and Large after All - Mario Larch; José-Antonio Monteiro; Roberta Piermartini; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2019)
We capitalize on the latest developments in the empirical structural gravity literature to revisit the question of whether and how much does GATT/WTO membership affect international trade. We are the first to capture the non-discriminatory nature of GATT/WTO commitments by measuring the effects of GATT/WTO membership on international trade relative to domestic sales. These unilateral effects of GATT/WTO membership are found to be large, positive, and statistically significant. We also obtain bilateral GATT/WTO estimates, which are larger than those reported in the literature. In particular, our results imply that, on average, joining GATT and/or WTO has increased trade between members by 171% and trade between member and non-member countries by about 88%. We also find that although both GATT/WTO has been effective in promoting trade between members, the WTO has been more effective in promoting trade with non-members than GATT. A battery of sensitivity experiments confirms the effectiveness of our methods and robustness of our main findings.
Keywords: F13; F14; F16; 330; GATT/WTO; international trade; domestic sales; structural gravity